Playful pedagogy for deeper learning: exploring the implementation of the play-based foundation phase in Wales. Issue 1 (2nd January 2020) - Wainwright, Nalda; Goodway, Jackie; Whitehead, Margaret; Williams, Andy; Kirk, David
ABSTRACT: The Welsh foundation phase is a play-based curriculum for 3–7-year-olds advocating outdoor and experiential approaches to learning. Play-based outdoor learning increases interaction with a range of affordances giving opportunities for movement in learning. Children assign activities as either play or not play-based on a series of cues. Teaching approaches that incorporate cues associated with play can influence pupil engagement and involvement in learning. This paper draws on data from a three-year study of the implementation of the foundation phase. Analysis of data from observations, field notes and video suggest pupils were more involved in tasks with higher levels of well-being when tasks were perceived as play. Leavres suggests increased involvement in learning may result in deeper learning.